OPTIMALISASI LITERASI DALAM MENINGKATKAN INKLUSI KEUANGAN SYARIAH DI ERA DIGITAL - Anggraini, Winda; Widyaningsih, Dwi Ayu; Wulandari; Rohmah, Rifka Nazilatur; Widodo, Wiki (ITB AAS Indonesia Surakarta, 2025)
The advancement of digital technology has transformed the landscape of financial services globally, including in the Islamic finance sector. Amid the rapid pace of digitalization, Islamic financial inclusion has become a strategic agenda to promote public access to financial products and services based on Sharia principles. However, the low level of Islamic financial literacy remains a significant obstacle in achieving optimal inclusion. This study aims to analyze the effect of Islamic financial literacy on Islamic financial inclusion in the digital era, with a case study in Pringsewu Regency. The research employs a quantitative approach through a survey of 400 purposively selected respondents. Regression analysis results indicate that Islamic financial literacy has a positive and significant effect on the level of digital Islamic financial inclusion, with a regression coefficient value of 0.705 and a significance level of 0.000. These findings suggest that improving literacy regarding Islamic financial products, contracts (akad), and fundamental values can strengthen public participation in the digital Islamic finance ecosystem. Therefore, collaboration among regulators, financial institutions, and educational institutions is essential to expand Sharia-based financial education through technology to achieve equitable and sustainable financial inclusion.